A Model of Competitive Impression Management: Edison versus Westinghouse in the War of the Currents. (December 2019) - Cole, Benjamin M.; Chandler, David
Organizational impression management theory traditionally explains how firms manage threats from specific events or from campaigns orchestrated by non-competitors, such as activists or regulators, but has not attempted to explain the complex dynamics of impression management campaigns orchestrated by a firm's competitor. To address this oversight, we analyze one of the bitterest rivalries in corporate history—the war of the currents between Thomas Edison and George Westinghouse, which ended in the triumph of Westinghouse's alternating current over Edison's direct current for electric power transmission. We define competitive impression management as activity by a firm or its employees that is intended to alter the perceptions of a competing firm or its offerings in the eyes of a common audience. By combining historical case study and grounded theory methods, our findings reveal that the war of the currents unfolded across distinct chronological stages dependent on the actions and reactions of others that were shaped by audiences' information filters. We explore the implications of our theory of campaigns and their consequences, expanding the scope of impression management theory, deepening our understanding of how organizations compete, and providing fertile ground for future research on market-based campaigns.